DEMOGRAPHIC AND SURGICAL EVALUATION OF TYPHOID ILEAL PERFORATION - Abro, Arshad Hussain; Siddiqui, Faisal Ghani; Ahmad, Sarfraz (Journal of Ayub Medical College Abbottabad, 2012)
Background: Typhoid perforation of small intestine is one of the most common causes of bowel perforation in the developing countries. The purpose of this study was to determine the prevalence, factors affecting prognosis, and optimal surgical management for typhoid perforation in Sindh. Method: One hundred and thirty patients with typhoid perforation were included in the study from July 2005 to June 2007 in the Department of Surgery, Liaquat University Hospital, Hyderabad. Patients were admitted as cases of acute abdomen. Detailed history, clinical examination and relevant investigations were carried out. Double layer primary closure, primary loop ileostomy and segmental resection with end-to-end anastomosis were performed according to the operative findings and condition of the patients. Attention was paid to postoperative complications and course of the morbid condition. Results: Majority of patients belonged to deserted areas of district Umerkot (n=35, 26.93%), and Mithi (n=20, 15.38%) followed by Dadu (n=17, 13.08%), Badin (n=15, 11.54%), Jamshoro (n=11, 8.46%), Hyderabad (n=10, 7.69%), Thatta (n=9, 6.92%), Mirpurkhas (n=7, 5.38%) and Sanghar (n=6, 4.62%). Double layer primary closure of single perforation was done in 50 (38.46%) patients, primary loop ileostomy was performed in 68 (52.30%) patients and primary resection and end-to-end anastomosis was performed in 12 (9.23%) patients. Postoperative complications were observed in 79 (60.76%) patients. Wound infection was the commonest complication seen in 70 (53.84%) patients followed by wound dehiscence in 10 (7.69%), faecal fistula in 9 (6.92%), septicaemia in 8 (6.15%), postoperative chest infection in 25 (19.23%), and intra abdominal abscess in 15 (11.53%) patients. Ten (7.69%) patients died due to septicaemia and other reasons. Conclusion: Typhoid perforation remains a frequently fatal illness with high prevalence in remote areas of Sindh. Primary loop illeostomy is the single most successful and life saving surgical procedure in terms of overall morbidity and mortality. Keywords: Typhoid perforation, demography, surgical procedure, end-to-end anastomosis, Sindh